Evelyn’s Sense of Meaninglessness in Her Existential Despair in Everything Everywhere All at Once Movie Script - Kirana, Kheista Sasi; Pasopati, Rommel Utungga (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article examines how the movie script Everything Everywhere All at Once by Daniel Kwan and Daniel Scheinert portrays one of the characteristics of existential despair: a sense of meaninglessness. A sense of meaninglessness is a situation when an individual is at a loss of meaning or feels there is no point in their existence. The movie tells the journey of Evelyn Wang, who feels helpless as she struggles to maintain her relationships, particularly with her husband and daughter, while also facing overwhelming responsibilities in her daily life. Through the lens of Søren Kierkegaard’s existential despair theory, this study analyzes how Evelyn’s experience reflects the crisis of meaning and self-identity. The research explores how her journey across multiple realities serves as a metaphor for her search for purpose and self-acceptance, ultimately questioning whether true meaning can be found amidst chaos. By applying an existentialist framework, this article aims to provide deeper insight into how Everything Everywhere All at Once illustrates the modern struggle with meaning, identity, and personal agency.